Mechanical Properties Enhancement in Potassium-Sodium Niobate Lead-free Piezoceramics: The impact of chemical modifications - Ramajo, Leandro Alfredo (2016)
The development of (K0.44Na0.52Li0.04)(Nb0.86Ta0.10Sb0.04)O3-based (KNL-NTS) ceramics is attracting great interest because of environmental concerns. Most of the efforts have been concentrated on improving the electrical properties. However, it is desirable to develop ceramics with good electrical response and high mechanical properties. Therefore, the evaluation of the mechanical properties is substantial and little studied. The aim of this work is to study the mechanical properties of KNL-NTS lead free ceramics doped with Zr evaluating the effects that can give rise to improved mechanical properties. Our results show that the crystalline phase, size and shape of grains in the ceramics are affected by the doping amount. We found that the microstructure does have a close relationship to the mechanical response, more specifically; a uniform and fine grain microstructure is suitable to lead high mechanical strength. Based on these results, the chemical modifications with Zr+4 ions have a significantly positive influence on hardness, strength and fracture toughness values of KNL-NTS ceramics.